Community-based respondent-driven sampling as a strategy for drug use surveillance in a large French urban area - Hélène Donnadieu; Catherine Quillet; Morgana D'Ottavi; Joëlle Castellani; Anne Debellefontaine; Sylvain Guichard; René Baglioni; Nicolas Langendorfer; Vincent Faucherre; Bertrand Hanslik; Edouard Tuaillon; Didier Laureillard; et al. (BMC, 2023)
Abstract Background Understanding drug use and behavior within the PWUD population is crucial to adapt harm reduction and prevention strategies, and provide improved addiction and medical treatment. However, in most countries such as France, the knowledge of drug use behaviors is likely biased as it originates from addiction centers which are attended by only an unknown proportion of PWUD. The objectives of this study were to describe drug use behavior in a population of active PWUD in the urban area of Montpellier, South of France. Methods We implemented a community-based respondent-driven sampling survey (RDSS), a validated strategy to obtain a representative sample of a population, to recruit PWUD in the city. Adult individuals reporting frequent psychoactive drug use other than cannabis, with confirmation by urine test, were eligible. Beside HCV and HIV testing, trained peers interviewed participants on their drug consumption and behavior using standardized questionnaires. Fifteen seeds launched the RDSS. Results During the 11 weeks of the RDSS, 554 actives PWUD were consecutively included. They were mostly men (78.8%), had a median age of 39 years, and only 25.6% had a stable living place. On average, participants consumed 4.7 (± 3.1) different drugs, and 42.6% smoked free-base cocaine. Unexpectedly, heroin and methamphetamine were consumed by 46.8% and 21.5% of participants, respectively. Among the 194 participants injecting drugs, 33% declared sharing their equipment. Conclusion This RDSS highlighted a high consumption of heroin, crack and methamphetamine in this PWUD population. These unexpected results can be explained by low attendance to addiction centers, the source of drug use reports. Despite free care and risk reduction equipment in the city, sharing was very frequent among injectors, challenging the current program of harm reduction.